Software Process Improvement - Models and Frameworks: Studying software process improvement models and frameworks such as CMMI, SPICE, and Agile maturity models for organizational excellence (Journal of Artificial Intelligence & Research, 2024)
Software development organizations constantly seek ways to improve their processes to deliver high-quality products efficiently. This paper explores various software process improvement (SPI) models and frameworks, including the Capability Maturity Model Integration (CMMI), Software Process Improvement and Capability Determination (SPICE), and Agile maturity models. The study aims to provide insights into the adoption, benefits, and challenges of these models for achieving organizational excellence. Through a comprehensive review and analysis, this paper highlights key considerations for selecting and implementing SPI models and frameworks, along with recommendations for successful SPI initiatives.